Potensi Kefir Susu Kambing dengan Penambahan Madu Randu dalam Mencegah Stress Oksidatif pada Tikus Diabetes : Potential of Randu Honey Kefir to Prevent Oxidative Stress in Diabetic Rats - Ibnu Malkan Bakhrul Ilmi; Avliya Quratul Marjan; Erna Harfiani; Indra Kusuma; Utami Wahyuningsih; Chika Nur Fikriana; Amelia Luthfiyah Mulyadewi (Universitas Airlangga, 2025)
Background: More than 90% of adults with type 2 diabetes are overweight or obese. This condition is known to increase oxidative stress, which contributes to cellular damage and disease complications. As a functional food, kefir has long been recognized for its various health benefits, including anti-inflammatory, antioxidant, and antidiabetic properties. Objectives: This study aimed to analyze the potential of randu honey kefir in preventing oxidative stress in diabetic rats. Methods: This study employed a randomized block design with a 21-day intervention period. A total of 42 male Sprague Dawley rats aged 6–8 weeks were divided into six groups: KS (standard), KN (negative control), K1 (quercetin), K2 (metformin), P1 (randu honey kefir 1.8 mL/200g BW), and P2 (preventive group). Diabetes was induced using streptozotocin at 40 mg/kgBW combined with a high-fat diet. Malondialdehyde (MDA) levels were analyzed using spectrophotometry, while interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) levels were measured using ELISA kits. Results: Significant differences (p-value<0.05) were observed in MDA, TNF-α, and IL-6 levels between the P1 and P2 groups compared with the KN group. Randu honey kefir groups showed mean oxidative stress marker levels comparable to those of quercetin and metformin treatments, including MDA (P1: 32.9 ± 29.35 nmol/mL; P2: 23.77 ± 11.63 nmol/mL), TNF-α (P1: 45.37 ± 31.25 pg/mL; P2: 37.81 ± 27.00 pg/mL), and IL-6 (P1: 64.81 ± 21.35 pg/mL; P2: 59.23 ± 14.95 pg/mL). Conclusions: Randu honey kefir intervention demonstrates potential in suppressing oxidative stress in diabetic rats.